Aspek Kelayakan Finansial Pengembangan Komoditas Asparagus (Asparagus officionalis) di Desa Pelaga, Kecamatan Petang, Kabupaten Badung - RAHAYU, NI WAYAN NITA; SUDARMA, I MADE; YUDHARI, I DEWA AYU SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.4, No.4, Oktober 2015, 2016)
Abstract Financial Aspects of the Development of Asparagus (Asparagus officionalis) in PelagaVillagePetangSub-District, Badung Regency Pelaga Sub-District Badung Regency is the only asparagus farm development in Bali. This asparagus development program was initiated by the Ministry of Cooperatives and SMEs through OVOP (One Village One Product). Badung Regency Government in cooperation with the Government of ICDF assist in providing product facilities in the form of seeds. This study focused on the financial feasibility of the development of farming asparagus in PelagaVillage based on agro-climatic conditions and constraints faced by farmers in its development. The results showed that from the financial aspects, the farming was feasible to be developed because the Net B / C ratio of Rp 2,21 Net Present Value had positive value of Rp 268.482.779, Internal Rate of Return of 35,87% and the Payback period was 3,7 years. The constraints faced by farmers in the development of the technical aspects of the asparagus farm that is the problem of pests and diseases that attack in the rainy season, from the economic aspect is lack of funds for the production process, and constraints of the social aspect is namely vegetable asparagus tends to only be consumed by the upper middle class society because price is relatively expensive. Keywords: Asparagus, Financial Analysis, Agro climate